Effect of Drought on Kharif Foodgrains Production : A Retrospect and Prospect - Venkateswarlu, J (Annals of Arid Zone, 2016)
The effect of drought on food grains production has been assessed on the national scale as well as for individual crops, taking state as a unit. But these are post cropping analyses. An early warning system was developed by Steyaert et al (1981) to assess the effect of drought on food grains production. The model evolved by Doorenbos and Kassam (1979) on "Yield response to water" can be used for assessing the proportionate of the potential achievable based on the rainfall as it progresses in relation to the phenology of the crop. In the monsoon food grains production, the perceptible effect of drought is more visible with rice and coarse cereals grown under better endownments. Some suggestions on tackling the high variability and almost plateauing that is taking place in food grains production in kharif season are made based on the responses available with the interventions (long and short term) at the government, farmer and researchers levels.